2018
DOI: 10.1016/j.ihj.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular disease risk factors: A community-based cross-sectional study in a peri-urban community of Kathmandu, Nepal

Abstract: BackgroundAs a low-income country, Nepal is experiencing cardiovascular diseases as an emerging health problem. However, studies are lacking on the risk factors of cardiovascular diseases in peri-urban communities; where the socio-demographical transition is in progress. Therefore, this study aimed to identify the prevalence and socio-demographic distribution of cardiovascular disease risk factors in one of the peri-urban communities in Kathmandu, Nepal.MethodsWe conducted a cross-sectional study in Sitapaila … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 30 publications
5
54
10
Order By: Relevance
“…In contrast, other studies showed that majority of the study participants were hypertensives. 4,7,15,18 In this study, majority of the cases and controls do not practice exercise regularly but no significant association was found with development of IHD. This is similar to study conducted by Mendagudali et al, Oommen et al at rural block of Vellore, Krishnan et al at rural block of Kerala and Dhungana et al at Sitapaila Village in Nepal.…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast, other studies showed that majority of the study participants were hypertensives. 4,7,15,18 In this study, majority of the cases and controls do not practice exercise regularly but no significant association was found with development of IHD. This is similar to study conducted by Mendagudali et al, Oommen et al at rural block of Vellore, Krishnan et al at rural block of Kerala and Dhungana et al at Sitapaila Village in Nepal.…”
Section: Discussioncontrasting
confidence: 60%
“…Nonetheless, the socio-cultural role of males in Nepalese society where their increased exposure to work and occupation, food and life-style related behavior compared to females who may not have similar exposure, further explains the higher risk of cardio-metabolic risk factors [31]. One associated factor within this study that sheds light on male's increased risk of cardiometabolic diseases is the higher consumption of tobacco and alcohol more than females [31,32]. Socioculturally in Nepal, males are at the forefront of earning money and managing the household expenditure.…”
Section: Males and Cardio-metabolic Riskmentioning
confidence: 77%
“…Socioculturally in Nepal, males are at the forefront of earning money and managing the household expenditure. Availability of cash money, together with the cultural bene ts due to patriarchy in Nepalese society can further explain the increased leeway for males that conduces the affordability for consumption of alcohol and tobacco [32]. These high-risk behaviors are further predicated on other factors such as level of education, occupation and the individual motivation towards healthy life style.…”
Section: Males and Cardio-metabolic Riskmentioning
confidence: 99%
“…Cardio vascular disease risk factors included smoking (17.6%), alcohol consumption (29.4%), insu cient fruit and vegetables intake (98%), insu cient physical activity (21.0%), obesity (15.3%), hypertension (34.4%), diabetes (10.5%) and high triglyceride levels (10.8%). The study concluded that there was high prevalence of cardio vascular risk factors among study respondents [26].…”
Section: Introductionmentioning
confidence: 89%